THE EFFECTIVENESS OF ANIMATION VIDEO ENTITLED â€œTHE BOY WHO CRIED WOLFâ€ TO IMPROVE STUDENTSâ€™ LISTENING SKILL OF NARRATIVE (An Experimental Research of Eighth Year Students of SMPN 1 Kejobong in the Academic Year of 2013/2014) (ELT Forum: Journal of English Language Teaching, 2014)
English is not an easy subject to learn. The reason is the quality of human resources or the teacher is still low. They have to teach and deliver their knowledge to the students, but they cannot deliver it well if they do not master English. They also have to be creative. Teaching will be more attractive if the teacher can deliver the materials in fun ways. This final project mainly aims at determining the effectiveness of using a video with texts in teaching listening for the eighth grade of junior high school students. The subject of this study was the eighth grade students of SMP Negeri 1 Kejobong in the academic year of 2013/2014. The number of the subject was 60 students. The design of this study was experimental study. The data were gained by administering pre-test and post-test of listening test. By using cluster random sampling, students of VIII E were taken as the samples of the experimental group and the samples of control group were the students of VIII G. In the pre-test, the mean score of the experimental group was 58.60, while the control group was 57.30. The result of post-test of the experimental group was 67.30 and the control one was 60.90. There was an improvement between the results of pre-test and post-test’s score. That meant that the medium was effective enough to be used in teaching listening of narrative. From the calculation of t-test, the result was 1.84 while the t-table with degree of freedom (df) 58, rounded up to 60 at 5% significance level was 1.67. Because the t-test was higher than the t-table (1.84>1.67), it can be concluded that using video with English texts was effective for teaching listening of narrative. An animation video can be made as a medium in teaching listening. The students will not get bored in the learning process because video is such an interesting medium which provides audio and visual that can grab the students’ interest. The teacher should consider animation videos in teaching listening because it is easy to understand the story by watching the animation videos which provides audio and visual.